Anticorpos anti-Leptospira spp. em animais selvagens do zoológico municipal de Ribeirão Preto, Estado de São Paulo, Brasil - Silva, Carolina dos Santos [UNESP]; Gírio, Raul José Silva [UNESP]; Guerra Neto, Guilherme [UNESP]; Brich, Michelle [UNESP]; Santana, Lucas Alves de Souza [UNESP]; Amâncio, Fábio Henrique; Mariani, Julia Rassi; Wessort, Pedro Meirelles Favaretto (My University, 2010)
Leptospirosis may affect all domestic and wild animals as well as human beings. Some serological studies have shown the involvement of wild species in the epidemiology of the disease. Once captive wild animals are not much studied, especially in Brazil, the present study aimed to detect anti- Leptospira spp. antibodies in animals from Ribeirão Preto city zoo, in São Paulo state, Brazil. Blood samples were collected from captive birds, fish, reptiles and mammals, sinanthropics and free-living animals and also from employees between March and October, 2006. Four hundred and three blood samples were obtained, 388 animals' samples (110 reptiles, 143 birds, 110 mammals and 25 fish) and 15 humans'. The sera were analysed by Microscopic Agglutination Test using 22 serovars from pathological leptospiras and two from non-pathological serovars. Among the animal samples, 339 were from captive animals, and 49 from free-living ones, captured with traps inside the zoo. One hundred and three (103/388 = 26.5%) samples reacted to leptospirosis, ninety-two (92/339 = 27.1%) samples were from captive animals and eleven (11/49 = 22.4%) from free-living ones. All humans' samples were negative. Serological titles varied from 40 to 5.120, with predominance of titles between 40 and 80 and the most frequent serovars were Patoc, Andamana, Canicola, Icterohaemorrhagiae and Panama.
Anti-Leptospira spp. antibodies in wild animals from Ribeirão Preto city zoo in São Paulo State, Brazil
Keywords: Leptospirosis; Serovars; Wild animals; Zoo; Animalia; Aves; Leptospira; Mammalia; Reptilia